Congenital dermoid cyst of the anterior fontanelle in Turkish children - Four case reports - Aslan, Ö; Özveren, F; Kotil, K; Özdemir, B; Kusçuoglu, U; Bilge, T (Japan Neurosurgical Soc, 2004)
Four cases of congenital inclusion dermoid cysts located over the anterior fontanelle occurred in male Turkish children aged 6 months to 5 years. These rare cysts presented as slow-growing soft masses over the anterior fontanelle. The cysts were totally removed without recurrence. Dermoid cysts can be easily cured because of the absence of intracranial extension.
Keywords: congenital dermoid cyst; inclusion cyst; anterior fontanelle